Arenas Blancas (El Hierro island), a new hotspot of plastic debris in the Canary Islands (Spain). (August 2021) - Hernández-Sánchez, Cintia; González-Sálamo, Javier; Díaz-Peña, Francisco J.; Fraile-Nuez, Eugenio; Hernández-Borges, Javier
Abstract: The present work has studied the incidence and type of micro (1–5 mm), meso (5–25 mm) and macroplastics (>25 mm) that have reached Arenas Blancas beach, located in the north coast of El Hierro island, in the Canary Islands (Spain), from October 2019 to May 2020 (13 sampling dates with 3 sampling points each). Taking into consideration the three studied plastic debris fractions (macro, meso and microplastics), a total of 9206 items were found, which had a total weight of 1169.7 g and a concentration of 891.3 ± 91.5 items/m 2 (118.3 ± 17.8 g/m 2 and 2.3 ± 0.4 g/L). Regarding their colour, most of them were transparent/white/clear, especially in the microplastic fraction in which they accounted for a 68% of the total. Attenuated Total Reflectance Fourier Transform Infrared spectroscopy of meso and microplastic fractions indicated that most of the particles were either polypropylene and polyethylene followed by polystyrene in a much lower amount. In general, the total amount of plastic debris that arrives to the beach by the persistent oceanic current pattern linked to the easternmost branch of the North Atlantic Subtropical Gyre is comparable to those of the most contaminated beaches of the Canary Islands archipelago, suggesting that a new hotspot of plastic debris arrival has been found. Highlights: Micro, meso and macroplastic fractions were studied between October 2019 and May 2020. 9206 items were found which had a total weight of 1169.7 g and a concentration of 891.3 ± 91.5 items/m 2 . Most of them were transparent/white/clear, especially microplastics (68% of the total). PP and PE were for the most abundant plastic composition. Results suggest that a new hotspot of plastic debris arrival has been found.